Practical moviemaking a handbook for the real world - Wallenstein, Joseph B. (McFarland & Co., 2012)
"This practical guide provides all necessary information for newcomers to the profession to get a movie made, information often left out of film school curriculums. Topics include finding a project, breaking down a script, creating a production board, casting, budgeting, scouting locations, scheduling, dealing with actors, establishing set protocol, and marketing. Real-life examples illustrate the subject"--Provided by publisher.